An Experimental Investigation of Fatigue Performance for A Flexure Spring - Bhoyar, Suraj; Sahare, Sudarshan; Bhojwani, Virendra; Sanap, Sudarshan; Kulkarni, Sunil (International Journal of Integrated Engineering, 2023)
In order to prevent a free-piston Stirling cryocooler failure during mission life, the flexure spring’s fatigue life is most critical and important. In the current research, an effort is made to examine fatigue life. The fatigue life testing of cryocooler flexures is frequently discussed in the literature. However, more information is needed about the economic approach and hardware needed for the testing. This research paper adopts the FEA approach of flexure spring and outlines the criteria for flexure fatigue testing. A moving coil linear motor was also designed and selected for the oscillating shaft and bending special-purpose flexure spring stack to validate stiffness criteria. The 108 no. of cycles required to validate the fatigue limit were also attained using the approach in a few days when testing at a relatively high frequency.